Sinergi Kepemimpinan Strategis dan Strategi Human Capital dalam Transformasi Organisasi: Studi Kasus PT Garuda Indonesia - Muzakki Darmawan; Akmal Reza Rakhili; Muhamad Riski Askha; Ziyan Abdurrahman Assahri; Alvin Alpha Rayhantama; Rony Edward Utama (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the role of strategic leadership in enhancing awareness and implementation of human capital strategy at PT Garuda Indonesia. A descriptive qualitative approach was employed to understand the dynamics of HR strategy implementation in the context of a national airline undergoing post-pandemic transformation. Data were collected through in-depth interviews, document analysis, and limited observations in the Human Capital division and operational units. The findings reveal that adaptive, communicative, and participatory strategic leadership significantly influences the effectiveness of human capital strategy. Key drivers of change include empowerment, consistent vision communication, and responsive leadership. Conversely, challenges such as budget constraints, perception gaps between management levels, and industry pressures affect strategy execution. The results indicate that synergy between leadership and human capital management is a crucial foundation for improving organizational performance and resilience. This study contributes both theoretically and practically to service organizations pursuing HR-based transformation.